Defining the prevalence and predictors of restrictive and obstructive airway pattern in a non-selected Malaysian population - Faisal AH,; Andrea Ban Yu-Lin,; Nina M,; Ahmad Izuanuddin I,; Tidi H, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
The incidence of chronic obstructive pulmonary disease (COPD) in Malaysia appear to be increasing. To date, there are no local studies describing restrictive and obstructive airflow limitation patterns using spirometry. We conducted a crosssectional study to determine the prevalence and predictors of airflow limitation symptoms by screening for COPD symptoms with the COPD Population Screener (COPD-PS) questionnaire and determined the airflow limitation using the new hand-held device, AirSmart®. We recruited 265 subjects. Eleven percent had restrictive pattern and 16% had obstructive pattern. Twenty percent of subjects had COPD-PS score of more than five. In the obstructive pattern group, 74% were active or ex-smokers (p=0.03, p<0.01), whilst those with restrictive pattern were more likely to be heavier with a body mass index (BMI) of more than 23 (OR 2.52, 95% CI: 1.02-5.62) (p<0.01). There was a negative correlation between forced vital capacity and BMI (r=-0.5813, p<0.001). We found a high prevalence restrictive pattern of airflow limitation using the new AirSmart® Spirometer. There appeared to be a large proportion of undiagnosed obstructive airway diseases and higher BMI could be the causes of limitation of airflow in our subjects.